Harmonisasi Peran Desa Sumberklampok dan Kepolisian Buleleng dalam Penanganan Kasus Penodaan Agama: Pendekatan Sosial dan Hukum - Anggara, Bayu; Suadnyana, I Nyoman Suadnyana; Widyani, Nyoman; Astrini, Ni Nyoman Raka (DOKTRINA: JOURNAL OF LAW, 2026)
As a countryrich in ethnic, religious, racial, and cultural diversity, Indonesia faces unique challenges, including blasphemy. Blasphemy involves insulting, desecrating, or misusing religious symbols and values, which has the potential to trigger horizontal conflict. Under Indonesian positive law, this is regulated by Article 156a of the Criminal Code (KUHP). This study focuses on a blasphemy case in Sumberklampok Village, Buleleng, Bali, involving the forced opening of the gate to West Bali National Park (TNBB) during Nyepi, a Hindu holy day. This incident caused social tension because it was perceived as undermining the traditional and religious values ​​of the local Hindu community. This study aims to analyze the harmonization of the roles of the traditional institutions of Sumberklampok Village and the Buleleng Police in handling this case through a descriptive qualitative approach. The results indicate that the harmonization of the roles of the traditional institutions of Sumberklampok Village and the Buleleng Police is crucial in resolving the conflict. Customary institutions play a role in mediation based on traditional values, while the Buleleng Police ensure transparent and fair law enforcement.